Addition of Riboflavin-Coupled Magnetic Beads Increases Current Production in Bioelectrochemical Systems via the Increased Formation of Anode-Biofilms - Arinda, Tutut; Philipp, Laura-Alina; Rehnlund, David; Edel, Miriam; Chodorski, Jonas; Stöckl, Markus; Holtmann, Dirk; Ulber, Roland; Gescher, Johannes; Sturm-Richter, Katrin (Frontiers in Microbiology, 2019)
Shewanella oneidensis is one of the best-understood model organisms for extracellular electron transfer. Endogenously produced and exported flavin molecules seem to play an important role in this process and mediate the connection between respiratory enzymes on the cell surface and the insoluble substrate by acting as electron shuttle and cytochrome-bound cofactor. Consequently, the addition of riboflavin to a bioelectrochemical system (BES) containing S. oneidensis cells as biocatalyst leads to a strong current increase. Still, an external application of riboflavin to increase current production in continuously operating bioelectrochemical systems does not seem to be applicable due to the constant washout of the soluble flavin compound. In this study, we developed a recyclable electron shuttle to overcome the limitation of mediator addition to BES. Riboflavin was coupled to magnetic beads that can easily be recycled from the medium. The effect on current production and cell distribution in a BES as well as the recovery rate and the stability of the beads was investigated. The addition of synthesized beads leads to a more than 2-fold higher current production, which was likely caused by increased biofilm production. Moreover, 90% of the flavin-coupled beads could be recovered from the bioelectrochemical systems using a magnetic separator.